Jejak Sejarah Keberadaan Desa Pekan Heran Kecamatan Rengat Barat - Refli Surya Bakara; Afrilia Mahdi; Dian Meisya Putri; Inez Pramulia Dewi; Keneisha Aulia Putri Akmal; M. Fikri Haykal; Umi Salimah; Yulian Gusmita (Departement of Mathematics Education, 2024)
The existence of this local history is due to the deep-rooted culture of the community and the many significant local events that became milestones in the development of the area itself. Pekan Heran Village as a small part of Indragiri Hulu holds historical traces and complex leadership dynamics throughout its existence, covering the colonial period, independence to the decentralization era, this then presents a unique perspective related to historical traces and the evolution of local leadership. In compiling this research, the researcher used a qualitative method with a descriptive approach. The researcher also used a historical approach as a process of critically testing and analyzing past phenomena as research objects which were then presented according to the facts. Pekan Heran Village is a village located in Rengat Barat District, Indragiri Hulu Regency, Riau, and is one of the oldest and largest villages on the banks of the Indragiri River. The collapse of the Srivijaya Kingdom has essentially become the cause of the release of small kingdoms under its rule, one of which is the Keritang Kingdom. Because the chaos that occurred in the Keritang Kingdom had been heard by King Narasinga in Malacca, the intention of Datuk Patih to pick up King Narasinga grew stronger, this intention was realized in an event, namely